Practical values of Village Libraries and Community Libraries in West Java - Yusuf, Pawit M; Saepuddin, Encang (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
The existence of the village library has a lot of value for the benefit of peoples lives, however, the values in question still needs to be expressed more real in peoples lives. The purpose of this study is to assess the values held by the village library and the public library in the village in West Java. Social values, the value of life, culture, history, communication and information, education, religion, preservation, symbol of civilization, archives, documentation, the value of continuity of knowledge between generations, and other values inherent to the function of the village library, are some examples of studies the focus of this study. The method used is the direct observation of village libraries and library communities in West Java. There are 13 village libraries sampled in this study. The results of this research illustrates that the presence of libraries in the villages received a positive response from the community at large. Libraries in the village has a lot of value benefits for many aspects of human life in the village. Some of these include social value, historical value, the value of documentation, and other values prevailing in society.